THE HERO SAGA: NARRATIVES ABOUT THE OLYMPIC ATHLETE SARAH MENEZES PRINTED IN THE NEWSPAPER OF PIAUÍ. (Fiep Bulletin - online, 2016)
In modern society, the media fulfill the collective imagination with archetypal figures and dominate sectors of daily life, including sport, transforming them into a great show. This study aimed to identify the accounts of the heroic saga of athlete Sarah Menezes in the 2012 Olympics in printed newspapers Piauí "O Dia", "Meio Norte" and "Diário do Povo". Qualitative nature study, descriptive, had the methodological procedure the Hero Saga model proposed by Campbell (1997) and the adaptation of Vogler (1998) to analyze the materials that portray the path of Olympic judoka. The corpus was delimited between the period of May 2012, when it was published the official list of members of the Brazilian national judo, and September 2012 when it was reported the participation of Sarah Menezes on Independence Day in Brasilia. The results show that the newspapers, even that unintentionally, narrated the path of Sarah Menezes due to her successful participation in the London Olympics, following the same structure of the mythological hero journey. The research findings allowed to identify the stage of "separation" or its accession to judo; the phase of "adventure" that matches the entire process of preparing for the big fight and his victory in the Olympics; and his "return" as heroin. It is concluded therefore that the narratives of heroic saga of Sarah Menezes contained in the three newspapers studied show their sports preparation towards the gold medal going through the phases that make up the saga of contemporary hero.
Keywords: Printed Media. Hero Saga. Judo. Sarah Menezes.